Impact of Identity on K-8 Mathematics - Aguire, Julia (National Council of Teachers of Mathematics, 2013)
Each teacher and student brings many identities to the classroom. What is their impact on the student's learning and the teacher's teaching of mathematics?This book invites K-8 teachers to reflect on their own and their students' multiple identities. Rich possibilities for learning result when teachers draw on these identities to offer high-quality, equity-based teaching to all students. Reflecting on identity and re-envisioning learning and teaching through this lens especially benefits students who have been marginalized by race, class, ethnicity, or gender. The authors encourage teachers to.